MicroRNAs as biomarkers for trastuzumab-based therapy in HER2-positive advanced oesophago-gastric cancer patients - Lote, Hazel; Mousoullou, Florentia; Vlachogiannis, George; Lampis, Andrea; Satchwell, Laura; Peckitt, Clare; Fong, Caroline; Begum, Ruwaida; Kidd, Shannon; Cromarty, Susan; Gordon, Anderley; Fribbens, Charlotte; et al. (Frontiers in Oncology, 2023)
This study aimed to identify microRNAs (miRs) as circulating biomarkers of resistance to firstline trastuzumab-based therapy in advanced HER2 positive oesophago-gastric cancer patients.A high-throughput 1015 Exiqon miRCURY LNA™ microRNA inhibitor library screen was performed in trastuzumab-treated HER2 positive NCI-N87 and HER2 negative FLO-1 oesophago-gastric cancer cell lines. NanoString nCounter ® miR analysis was performed in NCI-N87, FLO-1 and MAGIC trial (ISRCTN93793971) formalin-fixed paraffin-embedded (FFPE) oesophago-gastric cancer patient samples.MiR-148a-3p copies in plasma samples were quantified using Digital Droplet Polymerase Chain Reaction (ddPCR) from HER2 positive oesophago-gastric cancer patients treated with standard-of-care trastuzumab-based therapy within FOrMAT (NCT02112357) and PLATFORM (NCT02678182) clinical trials. Primary endpoints were overall survival (OS) plasma miR-148a-3p HIGH (>median) versus LOW (≤median); secondary endpoints were progression-free survival (PFS) and 3-month progression-free rates (PFR) miR-148a-3p HIGH versus LOW. PLATFORM sensitivity analysis normalised miR-148a-3p (NmiR-148a-3p).Inhibition of miR-148a-3p reduced NCI-N87 relative cell viability (<0.6) and expression was high (>242) in NCI-N87 and HER2 positive MAGIC trial patients (n=5).Normalised-miR-148a-3p (NmiR-148a-3p) LOW versus HIGH demonstrated a statistically significant difference in 3-month PFR (n=23, OR=0.